Maternal grand multiparity and intention to use modern contraceptives in Nigeria - Solanke, Bola Lukman (BMC Public Health, 2018)
BACKGROUND: Grand multiparity and low contraceptive prevalence are dominant among Nigerian women. These elevate the risk of unintended pregnancies, high-risk fertility and adverse maternal and child health outcomes among women in the country, particularly grand multiparous women. Studies have examined predictors of intention to use modern contraceptives among women of reproductive age. However, these studies did not ascertain the extent to which grand multiparity is associated with intention to use modern contraceptives. This study examined association between grand multiparity and intention to use modern contraceptives in Nigeria. METHODS: The study pooled data from 2003 to 2013 Nigeria Demographic and Health Surveys. The weighted sample size analysed was 34,302 women. The outcome variable was intention to use contraceptive. The main explanatory variable was parity with specific attention to grand multiparity. Unadjusted multinomial logistic regression coefficients were used to examine association between specific explanatory or control variables and intention to use contraceptives while the adjusted multinomial logistic regression was applied to further examine associated factors of intention to use contraceptives relative to being uncertain about future contraceptive use. Four multinomial logistic regression models were fitted using Stata 14. RESULTS: More than half of respondents do not intend to use contraceptives, while less than one-fifth of respondents intend to use contraceptives in the future. Across the four fitted models, the relative risks of intention to use compared with being uncertain about future contraceptive use were significantly lower among grand multiparous women. Results further revealed pregnancy termination, fertility planning status, exposure to mass media family planning messages, knowledge of modern contraceptives, ideal family size, remarriage, household power relations, and maternal education as other key factors influencing expected risk of intention to use contraceptives relative to being uncertain about future contraceptive use. CONCLUSION: Maternal grand multiparity is significantly associated with intention to use contraceptives among women in Nigeria. The development of a specific population and health programme to target grand multiparous women is imperative in the country. Such programme could be integrated into existing national family planning programme through specific contraceptive education, counselling and information for high parous women.